«БЕС ТАС» ОЙЫНЫ ҲӘМ ОНЫҢ ТӘРБИЯЛЫҚ ӘҲМИЙЕТИ - Әлеўов, Ө.; Пахратдинова, Т. (FAN va JAMIYAT, 2019)
The article is devoted to the description of Karakalpak national children’s game. «Bes tas» (five stones), that had been played by little girls since ancient times. The article contains information about the rules of the game, that requires good abilities to count, remember the numbers and elementary knowledge in Arithmetic’s. Such games are of a great importance in developing of children’s knowledge.